2011
DOI: 10.1021/jp1108703
|View full text |Cite
|
Sign up to set email alerts
|

A First-Principles Modeling of Ni Interactions on CeO2−ZrO2Mixed Oxide Solid Solutions

Abstract: We performed DFT+U quantum period calculations to study the characteristics of Ni interactions on/in CeO2−ZrO2 mixed oxide solid solutions. We analyzed the energetics of Ni adsorption and insertion on/in different surface and subsurface sites of the Ce0.25Zr0.75O2(111) slab, and also the changes in its atomic and electronic structures. The most stable interaction corresponds to a single Ni atom adsorbed on the O−O bridge site, where the nearest-neighbor metal atom is the Zr. Our calculations also show that Ni … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…One effective strategy to tackle these problems is to form ceria-based binary oxide solid solutions by doping with various transition, rare-earth or alkaline-earth elements. 2,4 It was 40 shown that incorporation of these metals into the CeO 2 lattice enhances its redox properties, OSC, and thermal stability. 2 For example, doping of CeO 2 with Zr resulted in the formation of a ceria-zirconia (CZ) solid solution that promoted its Ce 4+ /Ce 3+ redox couple, leading to an enhanced OSC, thermal resistance, in the literature on the preparation of SnO 2 modified CeO 2 -based binary oxide solid solutions as better ternary oxide catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One effective strategy to tackle these problems is to form ceria-based binary oxide solid solutions by doping with various transition, rare-earth or alkaline-earth elements. 2,4 It was 40 shown that incorporation of these metals into the CeO 2 lattice enhances its redox properties, OSC, and thermal stability. 2 For example, doping of CeO 2 with Zr resulted in the formation of a ceria-zirconia (CZ) solid solution that promoted its Ce 4+ /Ce 3+ redox couple, leading to an enhanced OSC, thermal resistance, in the literature on the preparation of SnO 2 modified CeO 2 -based binary oxide solid solutions as better ternary oxide catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…25 The optimized Ce 0.80 Hf 0.12 Sn 0.08 O 2-δ (CHS), Ce 0.80 Zr 0.12 Sn 0.08 O 2-δ (CZS), Ce 0.80 Pr 0.12 Sn 0.08 O 2-δ (CPS), and Ce 0.80 La 0.12 Sn 0.08 O 2-δ (CLS) (mol ratio based on oxides) ternary oxide solid solutions were synthesized by a coprecipitation method. In detail, the desired quantities (see Table S1, ESI †) of Ce(NO 3 ) 3 ·6H 2 O, 30 SnCl 4 ·5H 2 O, and other respective metal precursors such as HfCl 4 , ZrO(NO 3 ) 2 ·xH 2 O, Pr(NO 3 ) 3 ·6H 2 O, and La(NO 3 ) 3 ·6H 2 O were dissolved in distilled water separately and then mixed together for 1 h. Under constant stirring, aqueous ammonia solution was added dropwise to the mixture until the precipitation was 35 complete, at which point the pH was approximately 9.0. The resulting suspensions were stirred for another 12 h, aged for 24 h and then vacuum filtered.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work we have found that the most stable Ni interactions on the Ce 0.75 Zr 0.25 O 2 (111) surface corresponds to its deposition over OeO bridge sites [24]. These preferential Ni adsorption sites, named "W" and "X", are shown in Fig.…”
Section: Solid and Surface Modelsmentioning
confidence: 88%
“…Results and discussion [24]. For that purpose, we employed a superlattice consisting on 12 layers of Ce, Zr y O atoms and a vacuum space of approximately 13 Å .…”
mentioning
confidence: 99%
“…The interaction of copper with CeZr has been analyzed by TEM and spectroscopic methods showing that the base metal is able to interact strongly with the oxide surfaces and thus to facilitate its stability under the reaction conditions . For nickel, theoretical studies indicate that Zr favors the interaction of the base metal with the fluorite structure, the stabilization of the full oxidation state, as well as the production of oxygen vacancies . In general, the above‐mentioned contributions indicated an improved ceria redox performance as responsible for the enhancement of catalytic activity.…”
Section: Modification Of the M‐ceo2 Interface By The Presence Of Othmentioning
confidence: 99%